Compression of the vascular wall to create a friction fit in a vascular anastomotic coupler. (November 2021) - Nelson, John; Patel, Dev; Sant, Himanshu J.; Shea, Jill; Gale, Bruce K.; Agarwal, Jay
Abstract: A previously reported microvascular coupler was shown to effectively create vascular anastomoses, but was too large for practical clinical use. To safely reduce coupler size, certain failure modes needed to be better understood. The coupler functions, in part, by compressing the vessel wall between two concentric rings, creating a friction fit that anchors the device to the vessel. This work investigates the relationship between vessel wall compression and resulting friction fit strength to ensure reducing coupler size will not unduly increase the risk that this friction fit might fail. Vascular walls were compressed to a specified strain and the tensile force required to overcome the resulting friction was measured. Experiments were conducted with various vessel types (Porcine common carotid artery, splenic artery, and jugular vein), across a range of compressive strains (55–95%), and by using either PEEK or HDPE to compress the vessel. Tensile force was increased at a rate of 5 g/min or held constant for 24 h. For experiments with incrementally increasing force, the force at failure varied with compressive strain via a power function. At 70% compression, PEEK produced 4.6 times stronger friction fits than HDPE, and common carotid arteries and splenic arteries produced 1.8 and 1.3 times stronger fits than jugular veins respectively. For experiments where tensile force was applied for 24 h, much lower forces were required to overcome friction. These results were compared to friction fit failure in a coupler prototype and it was found that the prototypes failed at just 30% of the force required to cause vessel slip under the other test conditions. These results were used to develop a model that predicts the probability of device failure via vessel slipping (one design, smaller than previously reported, was estimated to fail at maximum in vivo axial stress once in 500 anastomoses, a potentially safe level of risk).